(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
Controlling a sizable output load with a relatively modest amount of control force is required in various applications. A device such as a mechanical power amplifier, which often responds promptly, may produce the desired effects in this context. Power can be made instantly available from the continually rotating drums of the mechanical power amplifier, depending on the requirements. This paper aimed to evaluate the amplification factor of mechanical power amplifiers for diverse rope materials like leather, woven cotton, and steel rope. A capstan mechanical amplifier-rope was used for the experiment. The experimental analysis showed that the power amplification factor is 2.23 for leather contact, 1.867 for woven cotton contact, and 1.32 for steel contact of rope. The experimental results show that leather amplifies more power than woven cotton or steel. Including a favorable amplification factor calculation, the results are strikingly compatible with experimental data.